Online Learning and COVID-19 in Higher Education: The Value of IT Models in Assessing Students' Satisfaction - Siti Norbaya Azizan* (Kassel University Press, 2022)
In online learning, students’ 'fit' (or satisfaction) with necessary technologies has become a vital component in assessing their learning efficacy, especially during the COVID-19 pandemic. While current studies have noted the impact of the curriculum, the instructor, and the learner, there is insufficient understanding of factors that predict students’ satisfaction with online learning during the crisis [38]. Existing studies focus on pre-pandemic circumstances, where online learning was a minor part of the higher education (HE) paradigm. This study assesses HE students’ use (i.e. 'fit') with online learning via their perception, behavioral intention, and satisfaction. By utilizing the Information Technology (IT) models of Task-Technology Fit (TTF) and Unified Theory of Acceptance and Use of Technology (UTAUT), the study investigates if, from students’ perspective, pedagogical theories are aligned with the IT models, using the quantitative survey method to gather input from students across various disciplines in a Singaporean university. Standard descriptive and correlation analyses studied the link between factors and their influence on online learning satisfaction. Significantly, the IT models are found to be valuable in assessing online learning satisfaction. Recommendations arising from the study provide helpful strategic guidelines for future online learning, which apply to Singapore and online learning design in general, particularly in this time of paradigm change.